Estudo da imobilização de celulase em géis de quitosana - Martins, Rafael Elias (Universidade Federal de São Carlos, 2007)
Cellulases are enzymes that catalyze the hydrolysis of cellulose producing glucose. Immobilization and stabilization of these enzymes could improve enzymatic process making it more attractive by reducing costs during their use. In this work, Celluclast (Novozymes A/S, Denmark) and CG 200 (Genencor) were immobilized into chitosan and into a chitosan/alginate hybrid support, after activation of the support with glutaraldehyde and glycidol under different conditions of immobilization such as temperature and pH. Immobilization process was evaluated by calculating the immobilization yield, coupling yield and thermal stability at 65°C. Temperature and pH optimum of enzymatic activity were analyzed as well. The best derivatives were obtained with chitosan alginate activated with glycidol, after immobilization at 27°C, pH 7.0, for 16 hours. The biocatalyst presented 56.3% of immobilization yield, 40.6% of coupling yield and it 11.2 fold more stable than free enzyme at 65°C. The temperature and pH for maximum activity of the derivatives and soluble enzyme was 60°C and 50°C, pH 2.5-3.0 and 4.2, respectively. Finally, the performance of the best biocatalyst developed in this work in the hydrolysis of sugarcane bagasse was compared to one observed using soluble enzyme. Although a higher conversion has been obtained with soluble enzyme in the beginning of the reaction, the immobilized enzyme allowed to reach a higher final conversion, 70%, than the one obtained with free Celluclast, 38.9%.
Keywords: Tecnologia de enzimas; Celulase; Imobilização; Quitosana; Bagaço de cana; Cellulase; Immobilization; Chitosan; Sodium alginate; Sugarcane bagasse; ENGENHARIAS::ENGENHARIA QUIMICA